(untitled) (Al-Academy, 2017)
After the twenty – first century become necessary for us motorcade era in educational a chevements by searching for the best strategies and teaching methods and techniques artotalbagesh resorting to the strategy Did not use in use in the teaching of the foreseeable material general by voice and teaching perspective for the student of the class fourth science In particular ,so the researcher asking the question follows: Can the peer education strategy to have an impact in perspective drawing skill development ? From here it demonstrated the importance of current research know the impact of peer education strategy in a skill perspective drawing for student fourth grade science for the academic (2015–2016)development be a socity current search of ( 85 ) female students for the Junior leader( Abdul Karim Kassem )in the district of (Essaouira-Wasit)Province , has a simple chose to deliberat for consideration consisted of(20)female student statistical analysiswas perfomed after her test application abash to achieve the null hypothesis using(Alajtbar Altaia) to search with the same two tests per kit turned out and gelthesela knowledge and skills after they realized the validity and reliability tests to apply education strategy to peer reached friendliness statistically significant differencesat the level of significance (0.05) when the degree of freedom (19) between the pre and post tests in the light of these results concluded researcher that peer education strategy in the subject ofpeer education more read than the way normal and reliable in the skill of perspective drawing for students fourth grade and scientific development to be some recommended by it is researcher need to use new strategies in teaching foreseeable material as the researcher has proposed a similar study for the current search other scholarships to various stages and materials.